Bioinspired NiO Nanospheres: Exploring In Vitro Toxicity Using Bm-17 and L. rohita Liver Cells, DNA Degradation, Docking, and Proposed Vacuolization Mechanism - Chouke, Prashant B. (2022)
The present work demonstrated a novel Cleome simplicifolia-mediated green fabrication of nickel oxide nanoparticles (NiO NPs) to explore in vitro toxicity in Bm-17 and Labeo rohita liver cells. As-fabricated bioinspired NiO NPs were characterized by several analytical techniques. X-ray diffraction (XRD) revealed a crystalline face-centered-cubic structure. Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible diffuse reflectance spectroscopy (UV-DRS), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS) confirmed NiO formation. The chemical composition was confirmed by energy-dispersive X-ray spectroscopy (EDS) and X-ray photoelectron spectroscopy. Brunauer-Emmett-Teller (BET) revealed the mesoporous nature. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) revealed the formation of 97 nm diameter nanospheres formed due to the congregation of 10 nm size particles. Atomic force microscopy (AFM) revealed the nearly isotropic behavior of NiO NPs. Further, a molecular docking study was performed to explore their toxicity by binding with genetic molecules, and it was found that the docking energy was about −9.65284 kcal/mol. On evaluating the in vitro toxicity of NiO NPs for Bm-17 cells, the study showed that when cells were treated with a high concentration of NPs, cells were affected severely by toxicity, while at a lower concentration, cells were affected slightly. Further, on using 50 μg/mL, quick deaths of cells were observed due to the formation of more vacuoles in the cells. The DNA degradation study revealed that NiO NPs are significantly responsible for DNA degradation. For further confirmation, trypan blue assay was observed for cell viability, and morphological assessment was performed using inverted tissue culture microscopy. Further, the cytotoxicity of NiO NPs in L. rohita liver cells was studied. No toxicity was observed at 1 mg/L of NiO NPs; however, when the concentration was 30 and 90 mg/L, dark and shrank hepatic parenchyma was observed. Hence, the main cause of cell lysis is the increased vacuolization in the cells. Thus, the present study suggests that the cytotoxicity induced by NiO NPs could be used in anticancer drugs.